2020
DOI: 10.1007/s40520-020-01631-y
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 and the elderly: insights into pathogenesis and clinical decision-making

Abstract: The elderly may represent a specific cluster of high-risk patients for developing COVID-19 with rapidly progressive clinical deterioration. Indeed, in older individuals, immunosenescence and comorbid disorders are more likely to promote viralinduced cytokine storm resulting in life-threatening respiratory failure and multisystemic involvement. Early diagnosis and individualized therapeutic management should be developed for elderly subjects based on personal medical history and polypharmacotherapy. Our review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
296
4
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(365 citation statements)
references
References 122 publications
14
296
4
15
Order By: Relevance
“…In older individuals, comorbidities, such as hypertension, diabetes, obesity, and heart disease, are more likely to promote a cytokine storm resulting in life-threatening respiratory failure and multi-organ damage. 38 42 43 44 Also, respiratory distress is common among most late-stage Alzheimer's disease (AD) patients. 45 Bauer claims that individuals with dementia are more likely to have cardiovascular disease, diabetes, and pneumonia compared to individuals of the same age without dementia.…”
Section: Impact Of Covid-19 On Patients With Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In older individuals, comorbidities, such as hypertension, diabetes, obesity, and heart disease, are more likely to promote a cytokine storm resulting in life-threatening respiratory failure and multi-organ damage. 38 42 43 44 Also, respiratory distress is common among most late-stage Alzheimer's disease (AD) patients. 45 Bauer claims that individuals with dementia are more likely to have cardiovascular disease, diabetes, and pneumonia compared to individuals of the same age without dementia.…”
Section: Impact Of Covid-19 On Patients With Cognitive Impairmentmentioning
confidence: 99%
“…In some countries, overwhelming numbers of COVID-19 patients have caused shortages of hospital beds and ventilators, and, consequently, elderly patients with dementia have been relegated to the post-care ranking of critical care. 41 43 This disaster could be repeated if early prevention or control of an outbreak fails. Conversely, we propose that vulnerable parties should be given priority of care to prevent these failures in the future.…”
Section: Strategy For Managing Dementia During the Covid-19 Pandemicsmentioning
confidence: 99%
“…It is thought that a robust and persistent immune response may lead to an overproduction of inflammatory cytokines, causing damage to host tissues [ 10 ]. Reports have shown that, in the later stages of COVID-19 infection, cytokine storm is likely a major cause of disease progression [ 6 , 10 ] In addition, the elderly tend to exhibit chronic low-grade inflammation which develops from the continual production of inflammatory mediators and cytokines, thereby lowering the threshold to develop cytokine storm during COVID-19 infection [ 11 ]. Since AGEP usually develops 24 hours after cephalosporin use, we theorize that our patient’s vigorous immune response to COVID-19 infection, combined with cefepime use, may have contributed to the delayed development of AGEP.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients are particularly vulnerable and susceptible to adverse clinical outcomes of COVID-19 including respiratory failure and death. 4 According to the Nursing Home COVID-19 Public File from data reported by nursing homes to the Centers for Disease Control and Prevention's (CDC) National Healthcare Safety Network, of 207,315 cases in the US nursing homes, 51,700 deaths (25%), have been reported. 5 In a review of over 9,000 nursing homes from the US, COVID-19 outbreaks were more related to facility size, location- with Massachusetts and New Jersey having the greatest number of affected facilities—and greater percentage of African American residents.…”
Section: Introductionmentioning
confidence: 99%